Shadows of empire the Indian nobility of Cusco, 1750-1825 - Garrett, David T. (Cambridge Latin American studies, 2005)
The Indian nobility of the Andes - largely descended from the Inca monarchs and other pre-conquest lords - occupied a crucial economic and political position in late colonial Andean society, a position widely accepted as legitimate until the Túpac Amaru rebellion. Shadows of Empire traces the history of this late colonial elite and examines the pre-conquest and colonial foundations of their privilege and authority. It brings to light the organization and the ideology of the Indian nobility in the bishopric of Cusco in the decades before the rebellion, and uses this nobility as a lens through which to study the internal organization and tension of late colonial Indian communities. The work analyzes the significance of the collapse of the Indian nobility, both repudiated by the Indian commons and the crown in the last years of Spanish rule, following the rebellion to the emergence of the creole-dominated republican order after 1825